Buckling of open section composite columns - Dai, Guilong (2019)
The main objective of the project is to predict the failure load of open section columns. Composite column offers lighter weight but higher strength and higher stiffness compared to metal parts. Because of the unique property: high stiffness and high strength but light weight, more and more composite materials have been applied in the structural materials in aerospace industry, automobile industry and other sports parts. In this report provides details of using ANSYS Workbench to conduct buckling analysis for Aluminum I section and composite (Epoxy Carbon UD Prepreg (230 GPa)) columns. The linear analysis for the aluminum I section is conducted for 4 types buckling conditions in the study. The Euler buckling force for aluminum columns obtained by the software is around the theoretical values for all buckling ends conditions. From the study, it can be known that the local buckling occurs first followed by the global buckling. This shows that the Euler buckling force is much higher than local buckling force. The composite columns with same parameters (I sections, length) are investigated. It can be sure that the Euler buckling load is higher than those of aluminum column are. The non-linear analysis is also studied, and the force vs displacement curve is plotted. The non-linear analysis is much closer to the real value in theoretical.